Pengaruh Umm Al-Barahin Karangan Al-Sanusi dalam Penulisan Karya Akidah di Alam Melayu - Engku Wok Zin, Engku Ku Hassan; Hamat, Mohd Fauzi (Jurnal Usuluddin, 2009)
This article attempts to discuss the influence of Umm al-Barahin on the writings of al-Sanusi in creating an expression of theology in Malay world. The biography of al-Sanusi as writer of Umm al-Barahin kitab expounded in this article concisely. He is al-Asya`irah prominent figure who has been respected in the ninth century Hijrah. His writing, Umm al-Barahin influenced most of the writings on theology after his demise especially in the Malay world. The expressions of theology in the Malay world can be construed as bound with this Umm al-Barahin framework. The content of this debate, the arrangement of the content together with method of arguments are the same as used by al-Sanusi in Umm al-Barahin kitab.